Rumaket Sambung Roso: Makna Akuntansi Utang Piutang pada Praktik Arisan di Desa Jogodalu Kecamatan Benjeng Kabupaten Gresik - Rosylia Dwi Safitri; Syaiful Syaiful (Akuntansi, 2025)
This research aims to analyze the meaning of accounts payable and receivable accounting in social gathering practices in Jogodalu Village, Benjeng District, Gresik Regency. The method used is qualitative research with a phenomenological approach. Data sources consist of primary data obtained through interviews with informants involved in social gathering practices, as well as secondary data from books and literature analysis. Data collection techniques include interviews, observation and documentation. There were five informants selected, including arisan managers, arisan members, arisan members involved in arisan buying and selling transactions, as well as local community and religious leaders. The research results show five meanings in the practice of arisan in Jogodalu Village, Benjeng District, Gresik Regency, namely: arisan as a means of saving and investment for members, the concept of debts and receivables in arisan, buying and selling transactions in arisan as a financial emergency solution, the role of arisan in maintaining ancestral traditions, and as a form of Islamic brotherhood. This research confirms that social gathering is not only related to financial aspects but also about solidarity and support in society.